Primary Education Undergraduates’ Awareness and Perception on The Utilization of Open Educational Resources for Learning in University of Ilorin - Agarry, Rachael Ojima; Omolafe, Eyiyemi Veronica; Babalola, Ebenezer Omolafe; Aladesusi, Gboyega Ayodeji (ASEAN Journal of Educational Research and Technology, 2023)
This study investigated the awareness and perception of the utilization of Open Educational Resources (OER) for learning among primary education undergraduates at the University of Ilorin. The study adopted the descriptive research of survey type. This study was limited to the primary education undergraduate students in the Adult and Primary Education Department, University of Ilorin. 150 undergraduates were randomly selected from the department. Structured questionnaires were used to elicit a response from the respondents. The finding of this study shows that undergraduate students are aware of OER's learning tools. Primary education undergraduate students’ perception towards OERs tool for learning is positive, there are factors inhibiting effective use of OER for learning among students, undergraduate students used OERs site for learning, and there was no significant difference between male and female undergraduates’ perception of OER tools for learning. Based on the findings of this research, the following recommendation was made. Lecturers should endeavor to put their scholastic publications in the public domain of their institutions, as this will help the student to lay hands on more quality materials and the government should provide funds to ensure the stability of the OER movement.